Mean-field phenomenology of wetting in nanogrooves - Yatsyshin,P; Kalliadasis,S (Molecular Physics, 2016)
In this special issue article, we bring together our recent research on wetting in confinement, in particular planar walls, wedges, capillary grooves and slit pores, with emphasis on phase transitions and competition between wetting, filling and condensation, and highlight their similarities and disparities. The results presented are obtained with the classical density functional theory (DFT) for fluids, which is a mean-field statistical mechanical framework for including the spatial variations of the fluid density into the thermodynamic equation of state. For wetting in sculpted substrates, we solve numerically the DFT equations to obtain the fluid density profiles, wetting isotherms and phase diagrams. This allows us to contrast the wetting phenomenology of grooves, planar walls, slit and wedge-shaped pores. Of particular interest are the transitions associated with capillary condensation, planar pre-wetting and mean-field wedge pre-filling lines.